Multiply

(-4x-3y) (5y-12z) =

(x2 + 8x + 7) ÷ (x + 6)=

Printable View

- November 26th 2009, 12:28 AMwestdivoMultiply
Multiply

(-4x-3y) (5y-12z) =

(x2 + 8x + 7) ÷ (x + 6)= - November 26th 2009, 02:23 AMHallsofIvy
Use the "distributive law", twice;

-4x(5y- 12z)- 3y(5y- 12z) is one use of it

-4x(5y)- 4x(12z)- 3y(5y)- 3y(-12z) is the second. Multiply those.

(x2 + 8x + 7) ÷ (x + 6)=[/QUOTE]

So this is . It should be obvious that x+ 6 is NOT a factor of the numerator (6 is not a factor of 7) so you cannot reduce it any more. - November 26th 2009, 03:20 AMstapel